PERSEPSI MAHASISWA AKUNTANSI TERHADAP ETIKA PROFESI AKUNTAN BERDASARKAN GENDER DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU - Nanik Verawati; Gusnardi Gusnardi; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine whether there are differences in accounting student perceptions between male and female students. The population in this study was 216 students. The type of data used in this study is primary data. The sample in this study was taken based on Slovin method, namely as many as 68 students consisting of 23 male and 45 female and using proportional random sampling technique. Data collection techniques using questionnaire retrieval.Data analysis using descriptive analysis and Independent Simple t-test. Based on the Independent Simple Test showed that there were no differences in perceptions between male and female accounting students towards accountant professional ethics with a significance value of 0.558 which is greater than decision making, ie 0.05Key Words: Perception, The Accountant Profession Ethics, Gender, University Student’s.